Latitudinal dependence of ground VLF transmitter wave power in the inner magnetosphere - Xia, Zhiyang; Chen, Lunjin; Gu, Wenyao; Horne, Richard B.; Miyoshi, Yoshizumi; Kasahara, Yoshiya; Kumamoto, Atsushi; Tsuchiya, Fuminori; Nakamura, Satoko; Kitahara, Masahiro; Shinohara, Iku (Frontiers in Astronomy and Space Sciences, 2023)
In this study, we use approximately 3 years of observations from the Exploration of energization and Radiation in Geospace (ERG) satellite to statistically study the meridional distribution of wave power from very-low-frequency (VLF) ground transmitters in the inner magnetosphere and analyze the corresponding latitudinal dependence. The results show that the mean intensity of NWC transmitter signals decreases as the transmitter emission propagates from the southern latitude (~-30°) region to the equator in the inner magnetosphere and then increases as the emission propagates to the northern latitude (~30°) region again. Similar latitudinal dependence can be found from the Van Allen Probes' observation with a narrower latitude range (~-20° to 0°). A ray-tracing simulation of the transmitter emission propagation is performed and reproduces a meridional wave power distribution similar to the observation. Similar latitudinal dependence can also be found for NAA, NLK and NLM transmitters.